Krömer, Ralf, “The Historical Development of Pontrjagin Duality”, in: R. Krömer und E. Haffner (Hgg.), Duality in 19th and 20th Century Mathematical Thinking, Cham: Birkhäuser 2024 (Science Networks. Historical Studies; 63), 291–353. - Peckhaus, Volker (zbMATH Open, Zbl. 079505172)

Krömer, Ralf, “The Historical Development of Pontrjagin Duality”, in: R. Krömer und E. Haffner (Hgg.), Duality in 19th and 20th Century Mathematical Thinking, Cham: Birkhäuser 2024 (Science Networks. Historical Studies; 63), 291–353. - Peckhaus, Volker (zbMATH Open, Zbl. 07951348)

Corry, Leo, “Von Neumann and Impossibility, from Gödel to EDVAC”, in: Mastering the History of Pure and Applied Mathematics – Essay in Honor of Jesper Lützen (De Gruyter Proc. Math.), De Gruyter. Berlin 2024, 75–99. - Peckhaus, Volker (Mathematical Reviews, MR4769331)

Costantini, Filippo, “Definitions by Abstraction and Leibniz’s Notion of Quantity”, Theoria 90 (2024), 240–255. - Peckhaus, Volker (Mathematical Reviews, MR4740767)

Robust and Efficient Hybrid Optimal Control via Gaussian Process Regression and Multiple Shooting With Experimental Validation on a Double Pendulum on a Cart - Hesse, Michael; Schwarzer, Luis; Timmermann, Julia; Trächtler, Ansgar (PAMM)
ABSTRACT In this contribution, we propose an innovative method for determining optimal control sequences for nonlinear systems with partially unknown dynamics, which further expands our previous work. Within the paradigm of model‐based design, the practicality and safety of commissioning feedforward controls and feedback controllers have priority. Our approach leverages probabilistic Gaussian processes to adjust for model inaccuracies from measured system data. This differs from conventional approaches that involve complicated analytical modeling and may entail a substantial time investment to acquire expertise and may prove impractical. Consequently, we address the limitations inherent in traditional design methodologies. Our research focuses on the formulation and solution of the hybrid 1 optimal control problem using probabilistic state predictions and multiple shooting. This ensures adaptability, data efficiency, and resilience against uncertainties in system dynamics. These attributes are empirically substantiated through experimental validation on a chaotic and highly sensitive dynamical system—a double pendulum on a cart. Our methodology unfolds as an iterative learning process, systematically exploring diverse controls, accumulating data within each iteration, and refining the control strategy until the desired task is accomplished. The adoption of the two‐degree‐of‐freedom control structure allows for the distinct consideration of the feedforward and the feedback control signal. For the latter, we employ a time‐variant, linear quadratic regulator (LQR) designed to stabilize the system around its target trajectory. Furthermore, we integrate a probabilistic long‐term prediction through the unscented transform, enabling systematic anticipation of safety‐critical violations. Detailed insights into relevant implementation aspects are provided. To ascertain the real‐world applicability, we present an exemplary application involving a double pendulum on a cart. The objective is to bring the pendulum arms from the lower stable to the upper unstable equilibrium by horizontally moving the cart and subsequently stabilize them. In this scenario, we assume that the centrifugal forces, crucial to the system dynamics, have not been accurately modeled and must be learned from data. Solving the control task took only 5 iterations and 1 h of computation time, which surpasses our previous work [2], where we used the purely data‐driven PILCO framework and required 27 iterations and 57 h of computation time. The time of interaction with the system decreased by and the computation time is lowered by . It demonstrates significant practical applicability for commissioning control systems.

Bolzano, Bernard, Miscellanea mathematica 22, hg. v. Jan Berg, besorgt von Edgar Morscher und Otto Neumaier, Frommann-Holzboog: Stuttgart-Bad Cannstatt 2024 (Bernard Bolzano-Gesamtausgabe; II.B.12.2) - Peckhaus, Volker (zbMATH Open, Zbl. 07963874)

studiVEMINT Mathematik-Online-Vorkurs jetzt mit 300 integrierten Lernvideos frei verfügbar - Biehler, Rolf; Liebendörfer, Michael; Schmitz, Angela; Reich, Birte (Mitteilungen der Deutschen Mathematiker-Vereinigung)

Research Directions in Software Supply Chain Security - Williams, Laurie; Benedetti, Giacomo; Hamer, Sivana; Paramitha, Ranindya; Rahman, Imranur; Tamanna, Mahzabin; Tystahl, Greg; Zahan, Nusrat; Morrison, Patrick; Acar, Yasemin; Cukier, Michel; Kästner, Christian; et al. (ACM Transactions on Software Engineering and Methodology)
Reusable software libraries, frameworks, and components, such as those provided by open source ecosystems and third-party suppliers, accelerate digital innovation. However, recent years have shown almost exponential growth in attackers leveraging these software artifacts to launch software supply chain attacks. Past well-known software supply chain attacks include the SolarWinds, log4j, and xz utils incidents. Supply chain attacks are considered to have three major attack vectors: through vulnerabilities and malware accidentally or intentionally injected into open source and third-party dependencies/components/containers ; by infiltrating the build infrastructure during the build and deployment processes; and through targeted techniques aimed at the humans involved in software development, such as through social engineering. Plummeting trust in the software supply chain could decelerate digital innovation if the software industry reduces its use of open source and third-party artifacts to reduce risks. This article contains perspectives and knowledge obtained from intentional outreach with practitioners to understand their practical challenges and from extensive research efforts. We then provide an overview of current research efforts to secure the software supply chain. Finally, we propose a future research agenda to close software supply chain attack vectors and support the software industry.

Smart Home Users’ Security and Privacy Perceptions and Actions Differ By Device Category: Results from a U.S. Survey - Haney, Julie M.; Acar, Yasemin; Li, Anna; Haney, Faith (Lecture Notes in Computer Science)

"It’s Time. Time for Digital Security.": An End User Study on Actionable Security and Privacy Advice - Rotthaler, Anna Lena; Ramulu, Harshini Sri; Simko, Lucy; Fahl, Sascha; Acar, Yasemin (IEEE Symposium on Security and Privacy, SP 2025, San Francisco, CA, USA, May 12-15, 2025)

More than Usability: Differential Access to Digital Security and Privacy - Buckmann, Annalina; Nold, Jan Magnus; Acar, Yasemin; Zou, Yixin (Twenty-First Symposium on Usable Privacy and Security, SOUPS 2025, Seattle, WA, USA, August 10-12, 2025)

S3C2 Summit 2024-09: Industry Secure Software Supply Chain Summit - Rahman, Imranur; Acar, Yasemin; Cukier, Michel; Enck, William; Kastner, Christian; Kapravelos, Alexandros; Wermke, Dominik; Williams, Laurie

S3C2 Summit 2024-08: Government Secure Supply Chain Summit - Miller, Courtney; Enck, William; Acar, Yasemin; Cukier, Michel; Kapravelos, Alexandros; Kastner, Christian; Wermke, Dominik; Williams, Laurie

From Paranoia to Compliance: The Bumpy Road of System Hardening Practices on Stack Exchange - Busch, Niklas; Klostermeyer, Philip; Klemmer, Jan H.; Acar, Yasemin; Fahl, Sascha

Wild bonobos experience unusually low bone resorption during early lactation relative to humans and other mammals - Behringer, Verena; Sonnweber, Ruth; Fruth, Barbara; Housman, Genevieve; Douglas, Pamela Heidi; Stevens, Jeroen M. G.; Hohmann, Gottfried; Kivell, Tracy L. (Evolutionary Human Sciences)
In mammals, pregnancy and lactation are marked by calcium stress and bone resorption, leading to reduced bone mineral density. In humans, these periods may partly explain the higher prevalence of osteoporosis in older women compared with men, but lactation patterns in modern humans may reflect cultural influences rather than natural conditions. The extent to which these findings apply to wild-living mammals remains unknown. We measured urinary C-terminal crosslinking telopeptide of Type I collagen (CTX-I) levels, a bone resorption marker, during pregnancy in wild and zoo-housed bonobos (Pan paniscus) and during lactation in wild bonobos. Studying wild-living primates such as bonobos can provide insights into ancestral reproductive adaptations. We found an increase in CTX-I levels towards the end of pregnancy in zoo-housed and primiparous wild females. Contrary to expectations, CTX-I levels during early lactation are lower than in other reproductive phases. This pattern diverges from the assumption that lactation increases bone resorption. Our findings suggest that wild bonobos may use physiological or behavioral strategies to modulate bone metabolism during lactation. These adaptations, shaped in natural environments, provide insight into evolutionary pressures on skeletal health and may inform strategies to mitigate bone loss in humans.
Keywords: Reproductive phase; Hominoid; CTX-I; Bone turnover markers; Pan paniscus; Bone density

Doing Gender Reflexionen im Lehramtsstudium - Steinhardt, Isabel (Förderung von Genderkompetenz in der Ausbildung von Lehrkräften)
Damit sich Lehramtsstudierende Genderkompetenz im Studium aneignen können, ist es zunächst notwendig, diese zur Reflexion über Gender anzuregen – so die These dieses Beitrags. Kompetenzen entstehen durch die Aneignung von Kenntnissen, Fähigkeiten, Fertigkeiten und Werthaltungen und sind an Sozialisationserfahrungen und damit inkorporierte Handlungsweisen und Normen gebunden Genderkompetenz ist notwendig, um Schülerinnen und Schülern gleiche Entwicklungschancen jenseits geschlechtsspezifischer Zuschreibungen zu ermöglichen und bei angehenden Lehrkräften umfassende Genderkompetenz zu etablieren. Dabei ist Gender sozial konstruiert, was als „doing gender“ bezeichnet wird. Der vorliegende Beitrag stellt ein Seminarkonzept vor, in dem über den Doing-Gender-Ansatz die alltägliche Herstellung von Geschlecht in den Mittelpunkt gerückt wird. Erst wenn – so die Grundannahme des Beitrags – verstanden ist, wie Geschlecht in der Gesellschaft über das Doing Gender (re)produziert wird, kann das Doing durch eigene Verhaltensänderungen verändert werden. Wie dies erreicht werden kann, wird im Folgenden dargestellt. Dazu wird zunächst das Seminarkonzept vorgestellt, in dem durch die Reflexion einer schulischen Situation, in die die Studierenden selbst involviert waren, das Doing Gender aufgedeckt wird. Anschließend wird eine Typologie von Situationen vorgestellt, die auf den Portfolios von fünf Seminaren (WS 21/22bis WS 23/24) basiert. Abschließend wird evaluiert, inwieweit ein Kompetenzerwerb in Bezug auf Gender im Seminar stattgefunden hat.
Keywords: Doing Gender; Lehramt; Kompetenzen

Would I regret being different? The influence of social norms on attitudes toward AI usage - Kornowicz, Jaroslaw; Pape, Maurice; Thommes, Kirsten (Arxiv)
Prior research shows that social norms can reduce algorithm aversion, but little is known about how such norms become established. Most accounts emphasize technological and individual determinants, yet AI adoption unfolds within organizational social contexts shaped by peers and supervisors. We ask whether the source of the norm-peers or supervisors-shapes AI usage behavior. This question is practically relevant for organizations seeking to promote effective AI adoption. We conducted an online vignette experiment, complemented by qualitative data on participants' feelings and justifications after (counter-)normative behavior. In line with the theory, counter-normative choices elicited higher regret than norm-adherent choices. On average, choosing AI increased regret compared to choosing an human. This aversion was weaker when AI use was presented as the prevailing norm, indicating a statistically significant interaction between AI use and an AI-favoring norm. Participants also attributed less blame to technology than to humans, which increased regret when AI was chosen over human expertise. Both peer and supervisor influence emerged as relevant factors, though contrary to expectations they did not significantly affect regret. Our findings suggest that regret aversion, embedded in social norms, is a central mechanism driving imitation in AI-related decision-making.

Energy- and material-efficient Ti-6Al-4V sheet part fabrication by the novel TISTRAQ-process, including resistance heating and tool-based quenching: Insights into test stand design and material potential - Pfeffer, Nina; Kaiser, Maximilian Alexander; Feix, Werner; Kälble, Nils; Merten, Mathias; Stark, Andreas; Haufe, Andre; Meyer, Thomas; Tröster, Thomas; Höppel, Heinz Werner (Materials Science and Engineering: A)

KI und Schreiben. (Praxis Deutsch)

Dynamic interface behavior in coupled plates: Investigating Lamb wave mode repulsion with a spring-based model - Nicolai, Marcel; Bulling, Jannis; Narayanan, M.M.; Zeipert, Henning; Prager, Jens; Henning, Bernd (Ultrasonics)